2020
DOI: 10.3390/en13051279
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Variable and Constant Loading for Mesophilic Food Waste Digestion in a Long-Term Experiment

Abstract: Operators of commercial anaerobic digestion (AD) plants frequently note the challenge of transferring research results to an industrial setting, especially in matching well-controlled laboratory studies at a constant organic loading rate (OLR) with full-scale digesters subject to day-to-day variation in loadings. This study compared the performance of food waste digesters at fluctuating and constant OLR. In a long-term experiment over nearly three years, variable daily OLR with a range as wide as 0 to 10.0 g V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This was explained by the inappropriate atmosphere caused by FW properties and particularly to the relatively low C:N ratio which hindered the anaerobes growth [55] [55]. Hence, mono-digestion of FW is more resistant with moderately low and constant OLRs [58], and basing on the current findings, 2.4 kg VS/m 3 .d was the optimal OLR ensuring a performant development of the process for FW 100 .…”
Section: Specific Biogas Yieldmentioning
confidence: 68%
“…This was explained by the inappropriate atmosphere caused by FW properties and particularly to the relatively low C:N ratio which hindered the anaerobes growth [55] [55]. Hence, mono-digestion of FW is more resistant with moderately low and constant OLRs [58], and basing on the current findings, 2.4 kg VS/m 3 .d was the optimal OLR ensuring a performant development of the process for FW 100 .…”
Section: Specific Biogas Yieldmentioning
confidence: 68%
“…In the same context, Kumar et al, (2015) revealed that under an OLR higher than 2 kg VS/m 3 •d, an intensive concentration of propionate hardly convertible to acetate caused FW anaerobic digestion failure, which might explain the R1 behavior during the current research [56]. Therefore, focusing on the OLR limitations, particularly for a large scale, mono-digestion of FW was more resistant with moderately low and constant OLRs [57,58]. One of the main objectives of this experimental work was to evaluate the effects of agricultural and industrial waste on FW anaerobic process performance operated at different OLRs.…”
Section: Effect Of Co-substrate Addition On Startup Conditions Of Fw-acodmentioning
confidence: 69%
“…As methanogens adapt poorly to pH fluctuations, either a high or a low pH had the same effects on microbes in terms of functional inhibition. Table 4 shows that an increase in OLR of 4 kg VS/m 3 •d was followed by an alkaline pH at about 8.16 ± 0.28, which might hinder methanogen progress with reference to Song et al, (2020), who reported that a pH range of 6.8-7.5 was required for healthy microbial growth [58]. Certainly, pH variation definitely impacted methanogenesis progress.…”
Section: Earlymentioning
confidence: 99%
“…Pasteurisation is still required for hygienisation purposes, but it is not an effective strategy to increase methane yield. When poor performance in AD of food waste is encountered, monitoring of trace elements and choice of adequate loading of the reactor are usually effective strategies to overcome this [63], while pre-treatment of the substrate is not a promising approach.…”
Section: Discussion Of the Results From The Digestion Experiments With Pasteurised And Unpasteurised Substratesmentioning
confidence: 99%